Visualisation in contract education and practice : The first 25 years - Haapio, Helena (Routledge, 2022)
Lawyers are often accused of making contracts complex and user-unfriendly: too verbose, expensive to make and manage, and impossible to implement for people who lack legal training. Many clients view contracts and lawyers as business obstacles rather than enablers. In recent years, voices calling for a major shift have started to be heard, and contract simplification and visualisation have gained momentum. In addition to applying their expertise within the profession, lawyers are increasingly participating in contract planning and management. They need to explain their views to others, often across multi-professional teams. Clients need guidance in how to react to contract proposals, how to respond, and how to frame and present their negotiation points. Technologists developing smart contracts or AI solutions need to understand what contracts mean. For the lawyer advising them it is not just about knowing the law, it is also about communicating, capturing agreements and objectives, and making the meaning of contracts and law visible. Future lawyers need knowledge, skills, and tools to help others understand and act upon their advice. They need to be prepared for contracts and law in action, not just in books. Visuals can improve communication and help in this endeavor. How can we prepare ourselves and our students for a world where contracts may need to be summarized, explained visually, or designed and not just drafted? Building on the author’s quarter-century work with visualisation in contract education and practice, this chapter illustrates why and how the world of contracting is changing and how future lawyers can be better equipped to both cope and contribute. The chapter shows, with examples, how visuals can be used to generate insights and understanding, prevent unnecessary disputes, and pave the path to next generation contracts.
Keywords: fi=Talousoikeus|en=Business Law|